The Role of Financial Services Authority in Monitoring Fraud in the Capital Market - Adzra Nazhifah; Muhammad Aras Prabowo; Kartini Laras Makmur (Trescode Green Organization, 2024)
Economic growth is supported by the expansion and development of Indonesia's capital market, under certain conditions. Investors are concerned about actions that could harm the Indonesian capital market. With its authority, Financial Services Authority (OJK) oversees stock market activities. This study aims to examine the conditions that occur in the Indonesian capital market and the role of the OJK in overseeing and regulating it. Descriptive qualitative research methodology was used, and literature review was the means of data collection. For analysis, the study utilized literature sources. The research findings show how OJK was used to oversee the Indonesian stock market between 2020 and 2023. In 2020, there were 4 stipulations set, followed by 110 stipulations in 2021, 162 exams with 54 penalties in 2022.